A Review of Sharia Economic Law on Gold Investment in the Gold Savings Feature in the Dana Application - Nur Rizqi Febriandika; Tiara Vergita Mahanani (ITB AAS INDONESIA Surakarta, 2023)
Gold investment is a promising activity in the future. This gold investment is also allowed by some scholars. Thus, this study analyzes the sharia suitability of the NABUNG E-Mas feature in the DANA application which has various products (Buying and Selling, Physical Gold Printing) with fatwas related to the review of the fatwa and related positive laws, namely from the Laws and Regulations that underlie the practice of Gold Investment. in Indonesia. For this purpose, in this study, the procedure for buying and selling gold online in the DANA application will be explained which can be a reference for users regarding its sharia compliance. The author uses a qualitative research method through a normative-empirical legal approach with literature studies to collect data sources. From this research, it can be concluded that all products in the NABUNG eMAS feature in the DANA application: buying and selling gold, saving gold, and physically printing gold are in compliance with the law and related fatwas.